Characterization and quantitation of polyphenolic compounds in Senna macranthera var pudibunda from the Northeast of Brazil - Maia, Irvila Ricarte de O.; Trevisan, Maria T.S.; Silva, Maria Goretti de V.; Breuer, Andrea; Owen, Robert (Natural product communications, 2019)
Until recently, there was a lack of information on the phytochemical composition of the taxon Senna. Recent reports show that Senna splendida, Senna gardneri, and Senna georcica are characterized by profiles dominated by flavonoids, naphthapyrones, and stilbenes. Here, we studied the phytochemical composition of Senna macranthera var pudibunda (Benth) Irwin & Barneby for comparison. A total of 26 polyphenolic compounds were identified in methanol extracts of various botanical parts of Senna macranthera var pudibunda (Benth.) Irwin & Barneby. The higher concentration (on a dry weight basis) of polyphenolic compounds was detected in the leaves (48.55 g/kg), bark (21.26 g/kg), and roots (17.08 g/kg), whereas a lower concentration of polyphenolic compounds was detected in the fruits (6.67 g/kg). The polyphenolic profiles of the various botanical parts were dominated by flavan-3-ols and flavan-3-ol dimers. The bark and roots contained only these components (100%), whereas flavonoids were also identified as minor components in the leaves (15.7%) and the fruits (5.6%), respectively. The flavan-3-ol conjugates comprised the well-known procyanidins, along with the rarely reported afzelechin, giobourtinidol and procassinidin dimers.